Establishment of judicial review and elements of its emergence in Egypt - al-Omran, Nayel Musa Shaker; Ansari, Abdul Haseeb (Inderscience Publishers, 2012)
This paper explores judicial review in the provision of judicial review in the Egyptian legal system, and explores the historical and political background as well as the reasons for the establishment of the judicial review for determining constitutionality of laws. This paper also examines the elements that have helped to develop this. Finally, this paper applies the case study methodology by choosing Egypt as being the first Arab country that authorised its courts, especially the Supreme Constitutional Court, the right to apply judicial control which aided in the establishment of the principles of separation of powers, the rule of law and the independence of judicial authority. The paper concludes that the process of judicial review has contributed the Egyptian legal system in manifest ways, especially in development of healthy laws and making judiciary a more or less independent body as it operates under the authority of the Minister of Justice. The authors have relied on the historical and descriptive as well as analytical research methodologies.